2019
DOI: 10.1016/j.jtcvs.2018.10.142
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality in older patients after ventricular assist device implantation: A national cohort study

Abstract: Objectives: To assess baseline patient characteristics and identify factors associated with in-hospital mortality after ventricular assist device (VAD) placement.Methods: Cross-sectional study using the National Inpatient Sample database from January 2010 to December 2014. Analyses were performed with sample weights provided by the National Inpatient Sample, which are reported AE the standard error of the mean.Results: Weighted samples yielded 15,021 AE 1111 patients who received a VAD. The mean age at time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Implantation of left ventricular assist devices (LVAD) has gained increasingly more popularity in the elderly [20]. Unfortunately, risk for perioperative morbidity and mortality is also significantly increased compared to younger patients with reported in-hospital mortality of up to 50% in patients of 65 years and older [20][21][22]. Therefore, this is also a unsatisfying alternative to HTx for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Implantation of left ventricular assist devices (LVAD) has gained increasingly more popularity in the elderly [20]. Unfortunately, risk for perioperative morbidity and mortality is also significantly increased compared to younger patients with reported in-hospital mortality of up to 50% in patients of 65 years and older [20][21][22]. Therefore, this is also a unsatisfying alternative to HTx for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…One analysis of the National Inpatient Sample found that in‐hospital mortality among recipients of LVAD was associated with age older than 65 years (OR = 1.76), as was female sex (OR = 1.27) . Among older patients, in‐hospital mortality increased from 17.2% to 48.2% when one or more high‐risk interventions (prolonged mechanical ventilation, hemodialysis, cardiac surgery, or extracorporeal membrane oxygenation) were performed prior to LVAD placement . Atluri et al found that age older than 70 years was an independent predictor for death, with overall survival of 75% at 1 year, 63% at 2 years, and 54% at 3 years .…”
Section: What Is the Effect Of Age On Outcomes?mentioning
confidence: 99%
“…What criteria should patients meet to be defined as frail, because no standard definition for frailty exists? Lindvall and colleagues 1 report worthy results about the in-hospital mortality of a very large cohort of patients included in the National Inpatient Sample and who underwent VAD implant between 2010 and 2014. The authors stratified patients according the age; patients older than age 65 years were defined as older.…”
Section: Francesco Formica MDmentioning
confidence: 99%